Prospective study of skin adnexal tumours for a period of two years in a tertiary care hospital - Sanapala, Sridevi; Suvvari, Jagadeeswari; K. Seeram, Satish; Kondapalli, Mounika; Masa, Suresh; Atla, Bhagyalakshmi (International Journal of Research in Medical Sciences, 2017)
Background: Skin adnexal tumours are rare tumours with complex histological patterns and variations and difficult to diagnose by histopathology only, so clinical history and presentation is necessary. The objective of the study was to correlate with age, sex, location, type of differentiation of adnexal tumours in our pathology department. Methods: The present study was a prospective study done in the department of pathology in Andhra medical college, King George Hospital, Visakhapatnam. A total of 51 cases were included in this study from January 2015 to December 2016. Specimens were formalin fixed and after adequately processing the sections were stained routinely with hematoxylin and eosin stain and properly evaluated for histopathological examination. Results: Out of these 51 cases, 88.24% (45 cases) were benign, and 11.76% (6 cases) were malignant tumours. Hair follicle differentiation were most common (35.3%) followed by sebaceous gland differentiation (31.37%) and sweat gland differentiation (29.41%). Conclusions: Benign adnexal tumours were most common than malignant tumours. Skin adnexal tumours are clinically often misdiagnosed, so histopathological examination remains gold standard for their correct diagnosis.